Harga Pokok Produksi Dan Titik Impas Pengolahan Ikan Kayu - M. Ramli; Syarifah Zuraidah (Universitas Riau, 2009)
This research aims to detect cost structure, Cost of goods manufactured,Profit level, Break even point, and fish processing investment elegibility. Analysisresult is known biggest cost in raw material cost (69,87%) and Labour cost(14,53%). Cost of goods manufactured as big as Rp 17.890, - /kg, With profit level20,09%. Sale break even point is achieved in Rp 6.052.699, - and Proper investmentis carried out.